Eight Session of Central comity of League of communist of Serbia: A view from Croatia - Diklić Momčilo (Sociološki Pregled, 2007)
Twenty years after the famous Eighth Session of the League of Communist of Serbia, author tries to question many of the myths constructed around it in the meantime. In his analysis he recalls forgotten perspective of the Croatian leadership of the time. Author remind us that Croatian communists perceived both factions of Serbian communists as equally nationalistic, and that Milosevic received support of all others republics for the change of Serbian constitution in 1989. He also insists on the fact that Croatians started their breaking of Yugoslavia with maspok already, and that they initiated creation of paramilitary formations in 1985 in emigration. His main thesis is that process of creation and dissolution of Yugoslavia has to be analyzed above all through developments of Serbian-Croatian relationships.